Religion and ecological sustainability in China - Miller, James; Yu, Dan; Veer, Peter van der (Routledge contemporary China series, 2014)
"This book sheds light on the social imagination of nature and environment in contemporary China. It demonstrates how the urgent debate on how to create an ecologically sustainable future for the world's most populous country is shaped by its complex engagement with religious traditions, competing visions of modernity and globalization, and by engagement with minority nationalities who live in areas of outstanding natural beauty on China's physical and social margins"--